Physical activity and anxiety with complaints of PMS in adolescents during the COVID-19 pandemic - Ni Ketut Alit Armini; Arinda Naimatuz Zahriya; Laily Hidayati; Kartika Indaswari Dewi (Intelektual Pustaka Media Utama, 2022)
Premenstrual syndrome (PMS) is a menstrual cycle disorder that frequently appears in women. As a result of the coronavirus disease 2019 (COVID-19) virus pandemic, the school from home program was implemented, which could affect physical activity and anxiety and therefore increase the incidence of PMS. This cross-sectional research analyzed the relationship between physical activity and anxiety with PMS in adolescents. The population was 221 adolescent girls in Surabaya, Indonesia. A consecutive sampling technique was used to select the 143 respondents. The independent variables were physical activity and anxiety while the dependent variable was PMS. The data was collected using a questionnaire and analyzed by the Spearman Rho test with a level of significance α<0.05. The results showed no significant correlation between physical activity and PMS among adolescents, however there was a significant correlation between anxiety and PMS in adolescents (p=0.000; r=0.463). Adolescents with anxiety have higher risk of PMS. The higher level of anxiety will be the more severe the symptoms of PMS.